Electro-catalytic material of carbon fiber anchored bimetallic nanoparticles as well as preparation method and application of electro-catalytic material
By in-situ doping bimetallic nanoparticles in carbon fibers, the existing electrocatalytic materials have been solved inadequate active sites and low stability when treating organic pollutants in water, and efficient degradation and cycling stability are achieved Improved, suitable for environmental pollutant treatment.
Patent Information
- Application Number
- CN202411550263.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-01
AI Technical Summary
When treating organic pollutants in water, existing electrocatalytic materials have problems such as insufficient active sites, high interface charge transfer resistance, agglomeration and masking of active components, cumbersome preparation methods and loss of active components, resulting in poor degradation effect and low stability. , hinder its application in the environmental field.
Electrocatalytic materials using carbon fiber to anchor bimetal nanoparticles, and dopant bimetal nanoparticles (iron oxide and manganese oxide) in situ doping them in carbon fibers through electrospinning technology, using manganese's oxygen adsorption ability and iron activation ability Achieve synergistic effects, reduce metal leaching and improve cycle stability.
It realizes efficient degradation of organic pollutants, reduces interface transfer resistance, improves cycle stability and anti-interference ability, enhances environmental adaptability, and significantly increases the specific surface area to increase the reaction space between pollutants and ROS.
Smart Images

Figure CN119263412A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental functional materials, and specifically relates to an electrocatalytic material of carbon fiber-anchored bimetallic nanoparticles and a preparation method and application thereof. Background Art
[0002] The rapid development of industry and agriculture has brought many conveniences and benefits to mankind and society, but it has also produced a large amount of wastewater containing difficult-to-degrade organic pollutants. These organic pollutants enter the water in a variety of ways, increasing environmental risks and posing challenges to existing water treatment technologies. Treatment methods for pollutants in water bodies include adsorption separation and oxidation conversion. Among them, electrocatalytic technology has the advantages of fast degradation rate, wide application range, simple operation, easy combination with other technologies, and reduction of secondary pollution. Therefore, it has good prospects in saving chemical energy, controlling pollution and obtaining clean water. Electrocatalysis mainly degrades pollutants in water by direct or indirect oxidation reactions near the electrode, and indirect oxidation generally plays a leading role. The composite of conductive carbon substrate and metal oxide can accelerate electron transfer and reduce metal leaching.
[0003] In recent years, researchers have developed electrocatalytic materials based on carbon nanotubes, graphene, and biochar. In addition, composite structures such as covalent organic frameworks and metal organic frameworks (MOFs) have also been widely studied. Cui et al. (ACS Catal. 2022, 12, 13334–13348) deposited a layer of graphene on the surface of oxyferric chloride, and the electrocatalytic activity was significantly enhanced. However, this treatment method has certain disadvantages, that is, it is difficult to directly disperse the metal oxides evenly on the chemically inert and hydrophobic carbon substrate. The necessary pretreatment process will reduce the mechanical strength and conductivity of the carrier, sacrificing some long-term stability. The electrospinning technology can be used to disperse the metal precursor into the spinning solution containing the carbon source. The in-situ doping strategy is expected to achieve the composite of carbon and metal oxides without destroying the carrier. Chinese invention patent CN116835720A discloses a nano zero-valent iron-based fiber electrode, its preparation method and application. However, since its spinning solution contains pre-prepared MOFs and carbon black particles that enhance conductivity, the metal active species are not grown and compounded in situ, and there are problems such as increased fiber diameter, reduced active sites and surface area, and MOFs aggregation, which in turn reduces the activity of the electrocatalytic material. Electrocatalytic degradation effect, energy consumption, cost, etc. are all related to electrocatalytic materials, but the electrocatalytic materials in existing research face many problems such as high interfacial charge transfer resistance, agglomeration and masking of active components, cumbersome preparation methods, and loss of active components, which hinder their application in the environmental field. It can be seen that the comprehensive improvement of the activity and stability of electrocatalytic materials still faces key technical bottlenecks. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide an electrocatalytic material of carbon fiber anchored bimetallic nanoparticles with multiple active sites, good cyclic stability, low metal leaching, and the ability to efficiently electrocatalyze the degradation of organic pollutants in water; another purpose of the present invention is to provide a preparation method and application of the electrocatalytic material.
[0005] Technical solution: The electrocatalytic material of carbon fiber anchored bimetallic nanoparticles of the present invention comprises carbon fiber and bimetallic nanoparticles, the bimetallic nanoparticles anchored by the carbon fiber are uniformly dispersed, and the bimetallic nanoparticles are a mixture of iron oxide and manganese oxide with a particle size less than 10 nm.
[0006] Preferably, the contents of iron and manganese in the electrocatalytic material of the carbon fiber-anchored bimetallic nanoparticles are both 2% to 3%.
[0007] Preferably, the iron oxide is at least one of Fe3O4 and Fe2O3; and the manganese oxide is MnO.
[0008] The method for preparing the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles of the present invention comprises the following steps:
[0009] (1) dissolving an iron source and a manganese source in an organic solvent, adding an organic polymer and stirring to obtain a precursor solution;
[0010] (2) Electrospinning is performed using a precursor solution. The organic polymer is pulled by the electric field into a jet shape and solidified, and the metal is anchored in situ in the fiber precursor.
[0011] (3) The fiber precursor is subjected to pre-oxidation and carbonization treatment in sequence to obtain an electrocatalytic material of carbon fiber anchored bimetallic nanoparticles.
[0012] Preferably, in step (1), the mass ratio of the iron source to the manganese source is 2:1 to 1:2; the total dosage of the iron source and the manganese source is 4wt% to 10wt% of the organic solvent; and the dosage of the organic polymer is 10wt% to 15wt% of the organic solvent.
[0013] Preferably, in step (1), the iron source is selected from at least one of ferric acetate, ferric chloride, ferric nitrate and ferric acetylacetonate; and the manganese source is selected from at least one of manganese acetate, manganese chloride, manganese nitrate and manganese acetylacetonate.
[0014] Preferably, in step (1), the organic polymer is selected from at least one of polyacrylonitrile (PAN), polyvinyl pyrrolidone (PVP), and polyethyleneimine (PEI).
[0015] Preferably, in step (1), the organic solvent is selected from at least one of N,N-dimethylformamide (DMF), ethanol and chloroform.
[0016] Preferably, in step (2), the electrospinning parameters are set as follows: voltage 16-22 kV, spinning solution flow rate 0.8-1.5 mL / min; the distance from the spinning needle tip to the drum is 12-18 cm, the drum speed is 600-1200 rpm; the temperature is room temperature, and the humidity is 25-35%.
[0017] Preferably, in step (3), the pre-oxidation is carried out in an air or oxygen atmosphere, heating the temperature to 200-300°C at a rate of 1-5°C / min, and keeping the temperature at 200-300°C for 1-2h; and the carbonization is carried out in an argon or nitrogen atmosphere, heating the temperature to 700-1000°C at a rate of 5-10°C / min, and keeping the temperature at 700-1000°C for 1-2h.
[0018] The invention discloses an application of the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles in treating organic pollutants in water.
[0019] Preferably, the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles is used as a cathode to efficiently degrade organic pollutants in water by activating O2 to form active oxygen species.
[0020] Technical principle: The present invention adopts an in-situ doping strategy and combines the bimetallic synergistic effect to produce an electrocatalytic material of carbon fiber-anchored bimetallic nanoparticles, which exhibits excellent performance in treating organic pollutants in wastewater. Specifically: (1) The metal salt is directly dispersed and stably disposed in a viscous polymer solution and extruded from a needle controlled by a pump. The electric field plays a stretching role on the one hand, making it jet-like, and on the other hand, promotes the volatilization of the solvent, making it solidify into long fibers. The fiber substrate anchors the metal species, and the growth of metal nanoparticles is restricted during subsequent heat treatment. (2) The bimetallic contributes to the main source of active sites. On the one hand, manganese doping improves the adsorption capacity of oxygen, and on the other hand, iron doping improves the activation capacity of oxygen. In addition, the atomic radius of iron and manganese is similar, and the combination of the two has a higher driving force, which promotes the rapid transfer of electrons and is conducive to the formation of more stable nanoparticles, thereby achieving bimetallic synergy.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0022] (1) The iron-manganese bimetallic oxides are uniformly dispersed in small sizes in the carbon substrate and tightly bound to it, which increases the active sites, reduces the interfacial transfer resistance, and accelerates electron transport.
[0023] (2) During the heat treatment process, the polymer is pyrolyzed to produce reducing gases, resulting in a material with a mesoporous structure, which further increases the specific surface area and can greatly increase the reaction space between pollutants and ROS, thus facilitating the efficient degradation of organic pollutants.
[0024] (3) Iron-manganese bimetallic oxides are anchored in carbon fibers, which improves the cyclic stability and significantly reduces the amount of metal leaching.
[0025] (4) The carbon fiber-coated iron-manganese bimetallic oxide has a synergistic effect, which not only improves the degradation effect of organic pollutants, but also enhances the anti-interference ability. It is less affected by the pH value of actual wastewater and complex components such as various inorganic salts, and its environmental adaptability is significantly enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a transmission electron microscope image of the carbon fiber anchored bimetallic nanoparticle electrocatalytic material in Example 2 of the present invention;
[0027] Figure 2 X-ray diffraction patterns of the electrocatalytic materials in Example 2 and Comparative Examples 1 to 3 of the present invention;
[0028] Figure 3 This is a diagram showing the degradation effect of the electrocatalytic materials in Example 2 of the present invention and Comparative Examples 1 to 3 on thiamethoxam in water;
[0029] Figure 4 This is a diagram showing the degradation effect of the electrocatalytic material in Examples 1 to 3 of the present invention on thiamethoxam in water;
[0030] Figure 5 The cyclic stability of the electrocatalytic material in Example 2 of the present invention in degrading thiamethoxam;
[0031] Figure 6 This is a graph showing the amount of metal leaching from the electrocatalytic material after multiple cycles in Example 2 of the present invention;
[0032] Figure 7 This is a diagram showing the degradation effect of the electrocatalytic material in Example 5 of the present invention on various organic pollutants in water;
[0033] Figure 8 This is a diagram showing the degradation effect of the electrocatalytic material in Example 5 of the present invention in the presence of inorganic salt ions;
[0034] Fig. 9 This is a diagram showing the degradation effect of the electrocatalytic material at different pH values in Example 5 of the present invention. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0036] Example 1
[0037] A method for preparing an electrocatalytic material of carbon fiber anchored bimetallic nanoparticles comprises the following steps:
[0038] (1) First, a spinning solution was prepared. Specifically, 0.26 g of ferric acetate and 0.53 g of manganese acetate were dissolved in 8.5 g of DMF, and ultrasonicated for 10 min. Then, 1.4 g of PAN was added and stirred at room temperature overnight to fully dissolve.
[0039] (2) After the spinning solution prepared in step (1) was subjected to ultrasonic defoaming treatment for 10 minutes, a 5 mL needleless syringe was transferred into the syringe, fixed on the syringe pump of the spinning machine, and electrospinning was performed to obtain fiber precursor. The electrospinning parameters were set as follows: voltage 20 kV, spinning solution flow rate 1.0 mL / min; the distance from the spinning needle tip to the drum was 15 cm, and the drum speed was 800 rpm; the temperature was room temperature, and the humidity was 35%.
[0040] (3) The fiber precursor obtained in step (2) is placed in a muffle furnace, heated to 250°C at a rate of 2°C / min, and kept warm for 1.5 hours for pre-oxidation treatment. Then the pre-oxidized brown-black fiber is taken out and placed in a tube furnace, heated to 800°C at a rate of 5°C / min in an argon atmosphere, and kept warm for 2 hours for carbonization treatment. An electrocatalytic material (Fe1Mn2@N-CNF) of carbon fiber anchored bimetallic nanoparticles is obtained.
[0041] Example 2
[0042] The remaining steps of this example are the same as those of Example 1, except that the mass ratio of the added iron source to the manganese source is changed to 1:1, that is, 0.4 g of iron acetate and 0.4 g of manganese acetate are added. The product is recorded as Fe1Mn1@N-CNF.
[0043] Example 3
[0044] The remaining steps of this example are the same as those of Example 1, except that the mass ratio of the added iron source to the manganese source is changed to 2:1, that is, 0.53 g of iron acetate and 0.26 g of manganese acetate are added. The product is recorded as Fe2Mn1@N-CNF.
[0045] Example 4
[0046] The remaining steps of this embodiment are the same as those of embodiment 2, with the only difference being that the organic polymer added is replaced by PVP from PAN, that is, 1.4 g of PVP is added.
[0047] Example 5
[0048] The remaining steps of this embodiment are the same as those of Embodiment 2, except that the added iron source and manganese source are replaced by ferric chloride and manganese chloride respectively from ferric acetate and manganese acetate.
[0049] Example 6
[0050] A method for preparing an electrocatalytic material of carbon fiber anchored bimetallic nanoparticles comprises the following steps:
[0051] (1) First, a spinning solution was prepared. Specifically, 0.4 g of ferric acetate and 0.4 g of manganese acetate were dissolved in 8.5 g of DMF, and ultrasonicated for 10 min. Then, 1.2 g of PAN was added and stirred at room temperature overnight to fully dissolve.
[0052] (2) After the spinning solution prepared in step (1) was subjected to ultrasonic defoaming treatment for 10 minutes, a 5 mL needle-free syringe was transferred into the syringe, fixed on the syringe pump of the spinning machine, and electrospinning was performed to obtain fiber precursor. The electrospinning parameters were set as follows: voltage 22 kV, spinning solution flow rate 1.5 mL / min; the distance from the spinning needle tip to the drum was 18 cm, and the drum speed was 1200 rpm; the temperature was room temperature, and the humidity was 35%.
[0053] (3) The fiber precursor obtained in step (2) is placed in a muffle furnace, heated to 250°C at a rate of 5°C / min, and kept warm for 1.5 hours for pre-oxidation treatment. Then, the pre-oxidized brown-black fiber is taken out and placed in a tube furnace, and heated to 900°C at a rate of 10°C / min in an argon atmosphere, and kept warm for 1.5 hours for carbonization treatment. The electrocatalytic material of carbon fiber anchored bimetallic nanoparticles is obtained.
[0054] Example 7
[0055] A method for preparing an electrocatalytic material of carbon fiber anchored bimetallic nanoparticles comprises the following steps:
[0056] (1) First, a spinning solution was prepared. Specifically, 0.11 g of ferric acetate and 0.22 g of manganese acetate were dissolved in 8.5 g of DMF, and ultrasonicated for 10 min. Then, 0.85 g of PEI was added and stirred at room temperature overnight to fully dissolve.
[0057] (2) After the spinning solution prepared in step (1) was subjected to ultrasonic defoaming treatment for 10 minutes, a 5 mL needleless syringe was transferred into the syringe, fixed on the syringe pump of the spinning machine, and electrospinning was performed to obtain fiber precursor. The electrospinning parameters were set as follows: voltage 16 kV, spinning solution flow rate 0.8 mL / min; the distance from the spinning needle tip to the drum was 12 cm, and the drum speed was 600 rpm; the temperature was room temperature, and the humidity was 25%.
[0058] (3) The fiber precursor obtained in step (2) is placed in a muffle furnace, heated to 230°C at a rate of 1°C / min, and kept warm for 1 hour for pre-oxidation treatment. Then, the pre-oxidized brown-black fiber is taken out and placed in a tube furnace, heated to 700°C at a rate of 5°C / min in an argon atmosphere, and kept warm for 1 hour for carbonization treatment. An electrocatalytic material of carbon fiber anchored bimetallic nanoparticles is obtained.
[0059] Example 8
[0060] A method for preparing an electrocatalytic material of carbon fiber anchored bimetallic nanoparticles comprises the following steps:
[0061] (1) First, prepare the spinning solution. The specific steps are as follows: dissolve 0.28 g of ferric acetate and 0.57 g of manganese acetate in 8.5 g of chloroform, ultrasonicate for 10 min, then add 1.28 g of PVP, stir overnight at room temperature, and fully dissolve.
[0062] (2) After the spinning solution prepared in step (1) was subjected to ultrasonic defoaming treatment for 10 minutes, a 5 mL needle-free syringe was transferred into the syringe, fixed on the syringe pump of the spinning machine, and electrospinning was performed to obtain fiber precursor. The electrospinning parameters were set as follows: voltage 22 kV, spinning solution flow rate 1.5 mL / min; the distance from the spinning needle tip to the drum was 18 cm, and the drum speed was 1200 rpm; the temperature was room temperature, and the humidity was 35%.
[0063] (3) The fiber precursor obtained in step (2) is placed in a muffle furnace, heated to 280°C at a rate of 5°C / min, and kept warm for 2 hours for pre-oxidation treatment. Then the pre-oxidized brown-black fiber is taken out and placed in a tube furnace, heated to 1000°C at a rate of 10°C / min in an argon atmosphere, and kept warm for 2 hours for carbonization treatment. An electrocatalytic material of carbon fiber anchored bimetallic nanoparticles is obtained.
[0064] Comparative Example 1
[0065] A method for preparing a carbon fiber electrocatalytic material. The remaining steps of this comparative example are the same as those of Example 1, except that no iron source and manganese source are added, and the product is recorded as N-CNF.
[0066] Comparative Example 2
[0067] A method for preparing an electrocatalytic material of carbon fiber anchored ultra-small iron oxide nanoparticles. The remaining steps of this comparative example are the same as those of Example 1, except that no manganese source is added, that is, only 0.8 g of ferric acetate is added, and the product is recorded as Fe@N-CNF.
[0068] Comparative Example 3
[0069] A method for preparing an electrocatalytic material of carbon fiber anchored ultra-small manganese oxide nanoparticles. The remaining steps of this comparative example are the same as those of Example 1, except that no iron source is added, that is, only 0.8 g of manganese acetate is added, and the product is recorded as Mn@N-CNF.
[0070] Application Example 1
[0071] Figure 1This is a transmission electron microscope image of the carbon fiber anchored bimetallic nanoparticle electrocatalytic material in Example 2 of the present invention; Figure 2 It is the X-ray diffraction pattern of the electrocatalytic materials in Example 2 and Comparative Examples 1 to 3 of the present invention.
[0072] The degradation effect of the electrocatalytic materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 on the organic pesticide thiamethoxam in water was investigated, and the specific method was as follows:
[0073] (1) Grind the material to be tested thoroughly in a mortar, weigh 6 mg of the ground material, and disperse it in a slurry. The slurry composition ratio is: 3% naphthol as a binder, 100 μL pure water and 400 μL anhydrous ethanol as a dispersion liquid. Ultrasonicate the prepared slurry for more than 40 minutes, drop-coat it on a hydrophobic carbon cloth (Bare CC), and dry it at room temperature for more than 4 hours to prepare an electrode sheet.
[0074] (2) The electrode sheet prepared in step (1) is used as the cathode in a three-electrode system, the anode is a platinum sheet, and the reference is a saturated calomel electrode. The reactor is a gas diffusion electrode, and oxygen flows through the side of the electrode sheet that is not loaded with material, and the gas flow rate is set to 10 mL / min.
[0075] (3) A 0.05 M Na2SO4 solution was prepared as the electrolyte, a 10 ppm thiamethoxam solution was prepared as the pollutant, the reaction system was 15 mL, and the initial pH was 5.7.
[0076] (4) The initial voltage was set to -0.5 V, and samples were taken at intervals to quench in quantitative methanol. The samples were filtered through a 0.45 μm microporous membrane filter, and the concentration changes of thiamethoxam were analyzed by high performance liquid chromatography to obtain the degradation efficiency of different materials. The results are shown in Figure 3 , 4 As shown, the doping and synergistic effect of the bimetallic oxides accelerated the degradation rate of pollutants compared with the control group.
[0077] Application Example 2
[0078] The cyclic stability of the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles prepared in Example 2 of the present invention in degrading thiamethoxam in water was investigated, and the specific method was as follows:
[0079] (1) Grind the material to be tested thoroughly in a mortar, weigh 6 mg of the ground material, and disperse it in a slurry. The slurry composition ratio is: 3% naphthol as a binder, 100 μL pure water and 400 μL anhydrous ethanol as a dispersion liquid. Ultrasonicate the prepared slurry for more than 40 minutes, drop-coat it on a hydrophobic carbon cloth, and dry it at room temperature for more than 4 hours to prepare an electrode sheet.
[0080] (2) The electrode sheet prepared in step (1) is used as the cathode in the three-electrode system, the anode is a platinum sheet, and the reference is a saturated calomel electrode. The reactor is a gas diffusion electrode, oxygen flows through the side of the electrode sheet that is not loaded with material, the gas flow rate is set to 10 mL / min, and the electrochemical workstation (Chenhua 760e) is connected.
[0081] (3) A 0.05 M Na2SO4 solution was prepared as the electrolyte, a 10 ppm thiamethoxam solution was prepared as the pollutant, the reaction system was 15 mL, and the initial pH was 5.7.
[0082] (4) The initial voltage was set to -0.5 V, and samples were taken at intervals to quench in quantitative methanol. After the samples were filtered through a 0.45 μm microporous membrane filter, the concentration changes of thiamethoxam were analyzed by high performance liquid chromatography to test the cyclic stability of the material's degradation effect on thiamethoxam.
[0083] (5) After the first reaction is completed, the post-reaction solution is poured out, and the sample is filtered through a 0.45 μm microporous membrane filter. The concentrations of iron ions and manganese ions in the tail sample are tested using an inductively coupled plasma luminometer to determine the amount of metal leaching.
[0084] (6) Gently rinse the surface of the electrode with ultrapure water three times, and repeat steps (3) to (5) ten times.
[0085] The results are as follows Figure 5 , 6 As shown, the degradation performance of the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles remained stable after ten cycles, and the metal leaching amount was extremely low.
[0086] Application Example 3
[0087] The broad spectrum of pollutant degradation of the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles prepared in Example 5 of the present invention was investigated. The electrocatalytic degradation steps were the same as those in Application Example 1, except that the organic pollutants were replaced by organic pesticides imidacloprid and acetamiprid; antibiotics sulfamethoxazole, ciprofloxacin, and carbamazepine; and the phenolic pollutant phenol.
[0088] Depend on Figure 7 It can be seen that the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles has a good treatment effect on a variety of difficult-to-degrade organic pollutants.
[0089] Application Example 4
[0090] The anti-interference property of the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles prepared in Example 5 of the present invention in degrading pollutants was investigated. The electrocatalytic degradation steps were the same as those in Application Example 1, except that 100 mM of various inorganic salts were added to the solution when preparing it, and the pH was adjusted to neutral. Figure 8As shown, the presence of inorganic salt ions has almost no inhibitory effect on the degradation effect, and the side reactions caused by the presence of certain ions accelerate the degradation.
[0091] Application Example 5
[0092] The anti-interference property of the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles prepared in Example 5 of the present invention in degrading pollutants was investigated. The electrocatalytic degradation steps were the same as those in Application Example 1, except that the initial pH of the solution was adjusted to 3.0, 5.8, 7.0, 9.0 and 11.0 respectively with H2SO4 and NaOH when preparing the solution. The degradation effect was as follows: Fig. 9 As shown, good degradation effect is maintained in the pH range of 3-11.
Claims
1. An electrocatalytic material of carbon fiber anchored bimetallic nanoparticles, characterized in that: The invention comprises carbon fibers and bimetallic nanoparticles. The bimetallic nanoparticles anchored by the carbon fibers are uniformly dispersed. The bimetallic nanoparticles are a mixture of iron oxide and manganese oxide with a particle size less than 10 nm.
2. The electrocatalytic material of carbon fiber anchored bimetallic nanoparticles according to claim 1, characterized in that: The iron oxide is at least one of Fe3O4 and Fe2O3; the manganese oxide is MnO.
3. A method for preparing the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles according to claim 1, characterized in that: The following steps are involved: (1) dissolving an iron source and a manganese source in an organic solvent, adding an organic polymer and stirring to obtain a precursor solution; (2) Electrospinning is performed using a precursor solution, where the organic polymer is pulled by the electric field into a jet-like shape and solidified, and the metal is anchored in situ in the fiber precursor; (3) The fiber precursor is subjected to pre-oxidation and carbonization treatment in sequence to obtain an electrocatalytic material of carbon fiber anchored bimetallic nanoparticles.
4. The method for preparing the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles according to claim 3, characterized in that: In step (1), the mass ratio of the iron source to the manganese source is 2:1 to 1:2; the total dosage of the iron source and the manganese source is 4wt% to 10wt% of the organic solvent; and the dosage of the organic polymer is 10wt% to 15wt% of the organic solvent.
5. The method for preparing the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles according to claim 3, characterized in that: In step (1), the iron source is selected from at least one of ferric acetate, ferric chloride, ferric nitrate, and ferric acetylacetonate; and the manganese source is selected from at least one of manganese acetate, manganese chloride, manganese nitrate, and manganese acetylacetonate.
6. The method for preparing the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles according to claim 3, characterized in that: In step (1), the organic polymer is selected from at least one of polyacrylonitrile (PAN), polyvinyl pyrrolidone (PVP), and polyethyleneimine (PEI).
7. The method for preparing the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles according to claim 3, characterized in that: In step (2), the electrospinning parameters are set as follows: voltage 16-22 kV, spinning solution flow rate 0.8-1.5 mL / min; the distance from the spinning needle tip to the drum is 12-18 cm, the drum speed is 600-1200 rpm; the temperature is room temperature, and the humidity is 25-35%.
8. The method for preparing the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles according to claim 3, characterized in that: In step (3), the pre-oxidation is carried out in an air or oxygen atmosphere, heating the temperature to 200-300°C at a rate of 1-5°C / min, and keeping the temperature at 200-300°C for 1-2h; the carbonization is carried out in an argon or nitrogen atmosphere, heating the temperature to 700-1000°C at a rate of 5-10°C / min, and keeping the temperature at 700-1000°C for 1-2h.
9. Use of the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles according to any one of claims 1 to 2 or the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles prepared by any one of the preparation methods of claims 3 to 8 in treating organic pollutants in water.
10. The use of the electrocatalytic material of carbon fiber anchored bimetallic nanoparticles according to claim 9, characterized in that: The electrocatalytic material of carbon fiber anchored bimetallic nanoparticles is used as a cathode to efficiently degrade organic pollutants in water by activating O2 to form active oxygen species.
Citation Information
Patent Citations
Nanometer zero-valent iron-based fiber electrode and preparation method and application thereof
CN116835720A
Carbon-containing metal catalyst, preparation method and application thereof
CN103227334A
Multi-shape Fe-Mn composite carbon nanofiber and preparation and application thereof
CN109935472A
Mn / Fe-coated PC modified cathode, preparation method and device and method for in-situ coupling electro-catalytic desalination through electro-Fenton
CN115536109A
Metal / carbon nanofiber persulfate catalyst, preparation method and application
CN115869934A
Cited By
Preparation method and application of in-situ electrochemical reconstructed ferro-manganese bimetallic electrode material
CN119797512A
Preparation method and application of in-situ electrochemical reconstruction of iron-manganese bimetallic electrode material
CN119797512B